Role of Guided Ultrasound in the Treatment of De Quervain Tenosynovitis by Local Steroid Infiltration - Danda, Raja Shekar (J Hand Microsurg, 2016)
Ultrasound guidance for steroid injection in de Quervain disease is useful in identifying the presence of subcompartments and effectively injecting the drug into tendon sheath. We prospectively studied 50 patients with features of de Quervain disease to determine the effectiveness of ultrasound in positioning of needle for steroid injection and effectiveness of single versus multiple injections in the presence of subcompartments. Scalp vein set was inserted into the tendon sheath under ultrasound guidance and sterile conditions. Mixture containing 1 mL of methylprednisolone 40 mg with 1 mL of 2% lignocaine was injected and the patient followed for 6 months. In patients having subcompartments, improvement was better when two separate injections into each subcompartment were given compared with single. Ultrasound guidance is helpful in identifying the existence of subcompartment and injecting the subcompartments separately. Scalp vein set may be very effective in ultrasound-guided injection. This is a level III study.